Delay Dementia in The Elderly: A Working Memory Training Program Based on Acceptance and Commitment Therapy - Punpoem, Nongnuch; Haenjohn, Juthamas; Supwirapakorn, Warakorn (Journal of The Royal Thai Army Nurses, 2023)
The objectives of this quasi-experimental research were to compare the level of working memory in the experimental group of older persons among before experiment, after experiment and follow-up and to compare the level of working memory of the elderly between the experimental and the control group in the after experiment and follow-up period. The subject in this study was sixty older persons who had no dementia and were voluntarily willing to participate the research project. Participants were screened by using the 2002 Mini-Mental State Exam (the 2002 MMSE in Thai version). A total of sixty participants were randomly selected and divided into two groups (the experimental group and the control group) by using the matching method based on the scores of the Corsi Block test. The research instruments used in this research consisted of 3 main parts: (i) The working memory training program for the elderly based on Acceptance and Commitment Therapy, (ii) Corsi Block Test, and (iii) Color Trial Test. The period of the study can be divided into three main periods: (i) before experiment, (ii) after experiment, and (iii) follow-up. The experimental group was trained by using the working memory training program while the control group was trained by using the normal teaching method designed by the elderly school. Data were analyzed by using Repeated-Measures Analysis of Variance: One between-subject variable and one within-subject variable and the post-hoc comparison using the Bonferroni method. The result showed that the elderly in the experimental group had a significantly higher level of working memory in the posttest and the follow-up period than that in the control group (p < .05). In addition, the finding revealed that the elderly in the experimental group had a significantly higher level of working memory in the posttest and the follow-up period than that in the control group (p < .05).